Education on the digital terrain : a case study exploring college athletes' perceptions of social-media training - Sanderson, Jimmy; Browning, Blair; Schmittel, Annelie (London : Human Kinetics, Inc., 2015)
College athletes are active on a variety of social-media platforms. As a result, most athletic departments require them to participate in social-media education. Although this practice is becoming more prominent, little research has explored how college athletes perceive such training. This case study explored college athletes' social-media use and their perceptions about social-media education. Semi structured interviews of 20 college athletes at a Division I university were conducted. Using social-cognitive theory as a framework, analysis revealed that while participants expressed a desire for social-media education, they indicated that most of the messages they receive about social media tend to be forgettable. Consequently, athletic departments need to take a more reflexive approach to social-media education that incorporates college athletes' feedback to optimize this instruction.
Originally published in Sanderson, J., Browning, B., & Schmittel, A. (2015). Education on the digital terrain: A case study exploring college athletes' perceptions of social-media training. International Journal of Sport Communication, 8(1), 103-124. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports -- Social aspects -- Case studies; College athletes -- Case studies; Social media -- Case studies